Design of an automobile tracking anti-theft system using GSM and GPS - Laxmi Behera, Bhagya; Satrusalya, Sarmistha (International Journal of Psychosocial Rehabilitation, 2025)
An automobile tracking system is an electronic gadget introduced in an automobile to empower the proprietor or an outsider to follow the automobile’s region. This paper proposed to plan an automobile tracking system that works by utilizing GPS and GSM innovation, which would be the least expensive source of automobile tracking and it would function as an anti-theft system. It is a system dependent on an embedded which is utilized for chasing and placing of any automobile by utilizing Global Positioning System (GPS) and Global system for mobile communication (GSM). This plan will consistently analyse a moving automobile and report the status of the automobile on request. For doing so a microcontroller is interfaced sequentially to a GSM Modem and GPS Receiver. A GSM modem is utilized to send the position (Latitude and Longitude) of the automobile from a remote place. The GPS modem will persistently give the information, for example, the latitude and longitude demonstrating the situation of the automobile. Similar information is sent to the mobile at the opposite end from where the location of the automobile is requested. At the point when the solicitation by the user is sent to the number at the GSM modem, the system consequently sends a reply to that mobile demonstrating the location of the automobile in the form of latitude and longitude.